Holly Leaf, Volume 2 Number 5 - Maryland State Normal School (My University, 1928)
The Holly Leaf was the monthly student newspaper at Salisbury University from 1926 to 1970.
Keywords: Maryland State Normal School; Student Newspaper; Salisbury (Md.); Maryland